Characterization of the complete chloroplast genome of Prosopis tamarugo (Prosopis, Leguminosae), an endangered endemic tree species from the Atacama Desert - Contreras-Díaz, Roberto; van den Brink, Liesbeth; Navarrete-Fuentes, María José; Arias-Aburto, Mariana (BOSQUE, 2021)
Prosopis tamarugo (Prosopis, Sect. Strombocarpa) is an important endangered tree species from the Atacama Desert (Chile). However, this species requires urgent conservation measures, for which it is necessary to evaluate their genetic diversity. Here, we present the characterization of the complete chloroplast genome of P. tamarugo; the first complete chloroplast of a species from the Strombocarpa section, obtained by next generation sequencing (NGS) methods. The complete chloroplast contains 161,575 bp and a total of 129 genes. A phylogenetic analysis of four Prosopis plastomes revealed that P. tamarugo is a sister species of the other Prosopis species albeit having smaller chloroplast sequence compared to those of other Prosopis species. Nine DNAcp markers were detected to distinguish between haplotypes. Therefore, the chloroplast sequence of P. tamarugo could be highly valuable for upcoming phylogenetic studies.